Analisis Of Qulity Control Product Damage At PT.Sinar Jaya Inti Mulya Kota Metro - Kurniawan, Lucky; Fitriani, Fitriani (Universitas Muhammadiyah Metro, 2021)
Damage products that are not in accordance with standards is a major problem for each company, because these problems will cause losses for the company as a result of increasing production costs and lower selling value of products. The quality control system carried out at PT. Sinar Jaya Inti Mulya is still lacking due to a lack of quality control personnel as well as machine maintenance and labor constraints. The purpose of this study was to determine the type and amount of damage that occurred and what factors caused the damage or deterioration of product quality. The method used in this research is explanatory survey method. This type of research is quantitative research with the object of research is product quality control and product damage. Data collection using interviews and documentation. The analytical tool used is to use C Chart analysis, Pareto Chart and Fishbone Analysis. The results of the C Chart analysis research showed that the amount of damage that occurred was still within tolerance limits. The number of product defects based on the order of the number is the highest due to the presence of foreign matter impurities, moisture content and free fatty acid content. The factors that influence product damage are mostly related to workers who do not supervise the production process and lack of quality control personnel as well as other causes such as raw materials and the environment. Keywords: Control of product quality, product damage